Process Simulation of Two-Stage Anaerobic Digestion for Methane Production. Issue 2 (4th March 2019) - Al-Rubaye, Haider; Karambelkar, Shruti; Shivashankaraiah, Manohar M.; Smith, Joseph D.
ABSTRACT: A process simulation model was developed for the anaerobic digestion (AD) process used for biogas generation. Aspen Plus software was used for this purpose. The developed model predicts the production of biogas from any substrate at any given process condition. This model was validated against a variety of industrial data on anaerobic digestion. The four steps (Hydrolysis, Acidogenesis, Acetogenesis, Methanogenesis) with a total of 46 reactions that represent the AD process were simulated with appropriate kinetics. Sensitivity analysis was implemented for 5, 10, 20 and 30% substrates concentrations to increase the methane share in the biogas by studying the effects of hydrogen addition, HRT and pressure. The developed model is flexible and predicts enhancement of methane composition by hydrogen injection qualitatively and quantitatively.